Analytical solutions for soil flushing through geotextiles considering filter cake and clogging - H. Y. Wang; X. W. Tang; Q. Tang; B. Bai (International Association of Lowland Technology, 2015)
Prefabricated vertical drains (PVDs) have been used in finegrained soils remediation system to provide a higher flow rate. However, the migration and accumulation of the fine particles in the soil result in the filter cake adjacent to the geotextile and the pore clogging in the geotextile. An analytical solution for soil flushing through a clogged geotextile with a filter cake is developed. The results obtained by the proposed analytical solution agree well with those obtained from the finite difference method. Results from an illustrative example indicate that the formation of a filter cake at the surface of a geotextile is far more disadvantageous to soil flushing than pore clogging within a geotextile. The 5-hour base concentration at the depth of z = 50 mm for the case just considering the pore clogging in the geotextile is just 1.06 times more than that assuming no filter cake and no pore clogging in the geotextile. When the pore clogging combined with a filter cake are considered, the 5-hour base concentration at the depth of z = 50 mm increases by a factor of approximately 4.94.